Utvärdering av Scanias basbilar : En studie för Scania Special Vehicles, Laxå Special Vehicles, Sala Brand och Floby Autokaross Rescue Systems - Gunnarsson, Mattias (2011)
This report evaluates Scanias rescue-vehicles used by the Swedish rescue service. The report is based on visits at the involved companies and a survey carried out at Luleå rescue service. The report shows that personnel at the rescue-service in Luleå are quite pleased with their vehicles. Many point of views and comments have been made, but in a more improving then criticizing way. Some critical points have been identified, and the most criticism is put on the louvers to the tool trays that are considered deficient in several respects. Also, technology considered too old by the rescue personnel is identified as a major limiting factor. Hopefully, this report will lead to a better knowledge by the participating companies about how the rescue-vehicles are considered by the Swedish rescue service. It may also be a tool in the improvement process made by the different companies to achieve even better rescue-vehicles in the future. Validerat; 20110902 (anonymous)